A Highly Sensitive Magnetic Field Sensor Based on a Tapered Microfiber - Zelong Ma; Yinping Miao; Yi Li; Hongming Zhang; Bin Li; Yanpeng Cao; Jianquan Yao (IEEE Photonics Journal, 2018)
A compact all-fiber magnetic field sensor based on the combination of a magnetic fluid and a nonadiabatic microfiber is experimentally demonstrated. By using a fusion splicer combined with an additional flame brushing, the nonadiabatic microfiber, with an abrupt taper, a small waist diameter and a long region, provides a strong evanescent field and a long sensitive distance. The result indicates that a sensitivity as high as 309.3 pm/Oe can be achieved in the range from 0 to 200 Oe. The designed nonadiabatic microfiber sensing structure suggests potential application as a tunable all-in-fiber photonic and other newly fashioned magneto-optical photonic devices.